Trending Topics in Multiple Sclerosis - Gonzalez-Quevedo, Alina (IntechOpen, 2016)
Multiple sclerosis (MS) is a chronic inflammatory disease characterized by progressive demyelination and neurodegeneration of the central nervous system (CNS), constituting the most common demyelinating disease of the CNS in humans. Although intensive research over many decades has unveiled many pathophysiological mechanisms in the development of MS, the cause is still unknown. Nevertheless, it does seem clear that genetic susceptibility and environmental factors play crucial roles. Trending Topics in Multiple Sclerosis is a book that provides an insight into some of the main problems currently debated in this area of research, focusing on topics that deal with genetic and environmental risk factors, pathophysiological mechanisms, neurocognitive findings, and neuroprotective strategies.